Method and system for monitoring, predicting and evaluating ecological drought of grassland basin - ZHOU QUANCHENG; ZHANG WEIJIE; LI WEI; WANG YIXUAN; WANG WENJUN; QUAN QIANG; ZHAO SHUIXIA; YIN HANG; WU YINGJIE; CHEN XIAOJUN; ZHAO QIAN; SUN LIXIN (2022)
The invention discloses a grassland basin ecological drought monitoring, predicting and evaluating method and system, and the method comprises the steps: starting an unmanned aerial vehicle to go to a preset monitoring region, so as to collect ecological information; preprocessing the ecological information to obtain drought data of the corresponding monitoring area; sending the drought data of each monitoring area to a cloud server for storage; and acquiring drought data stored in the cloud server, evaluating the current drought condition according to the drought data, and predicting the drought condition in a period of time in the future according to the drought data. The information of the grassland drainage basin is acquired by adopting the unmanned aerial vehicle, the drought condition can be determined based on the acquired information, a large amount of manpower is not required to be input for field data acquisition, the data can be ensured to be real and reliable, and the accuracy of monitoring, predi